Imaging of Enzyme Activity by Electron Paramagnetic Resonance: Concept and Experiment Using a Paramagnetic Substrate of Alkaline Phosphatase. (7th August 2018) - Sanzhaeva, Urikhan; Xu, Xuan; Guggilapu, Priyaankadevi; Tseytlin, Mark; Khramtsov, Valery V.; Driesschaert, Benoit
Abstract: Enzyme activities are well established biomarkers of many pathologies. Imaging enzyme activity directly in vivo may help to gain insight into the pathogenesis of various diseases but remains extremely challenging. In this communication, we report the use of EPR imaging (EPRI) in combination with a specially designed paramagnetic enzymatic substrate to map alkaline phosphatase activity with a high selectivity, thereby demonstrating the potential of EPRI to map enzyme activity.